Dynamics of indistinguishable free particles driven by a quantum bath - Nizama Mendoza, Marco Alfredo (2019)
Time evolution of correlations for two indistinguishable free particles, in a one-dimensional lattice interacting with a quantum bath have been studied in the Born-Markov approximation. The analytical solution for the density matrix is obtained, for bosons and fermions, in the second quantization formalism. Time-evolution of the negativity of indistinguishable particles is analyzed for quantum mixed states. Quantum correlations heavily depend on the selected bipartition, in return, a small difference between the statistics of the particles have been noted, due to the Pauli exclusion principle. In the presence of the dissipation, the negativity (a non-classical correlation) shows a time-oscillatory behavior for a particular geometrical bipartition. The total probability of finding one particle in each subsystem has also been calculated showing a consistent behavior.